A mindfulness-based intervention to control weight after bariatric surgery: Preliminary results from a randomized controlled pilot trial. (October 2016) - Chacko, Sara A.; Yeh, Gloria Y.; Davis, Roger B.; Wee, Christina C.
Highlights: We tested a mindfulness-based approach to control weight after bariatric surgery. The intervention was highly acceptable to bariatric patients. This approach may be effective for reducing emotional eating but not weight. Longer-term studies in the bariatric population may merit further exploration. Abstract: Objective: This study aimed to develop and test a novel mindfulness-based intervention (MBI) designed to control weight after bariatric surgery. Design: Randomized, controlled pilot trial. Setting: Beth Israel Deaconess Medical Center, Boston, MA, USA. Interventions: Bariatric patients 1–5 years post-surgery (n = 18) were randomized to receive a 10-week MBI or a standard intervention. Main outcome measures: Primary outcomes were feasibility and acceptability of the MBI. Secondary outcomes included changes in weight, eating behaviors, psychosocial outcomes, and metabolic and inflammatory biomarkers. Qualitative exit interviews were conducted post-intervention. Major themes were coded and extracted. Results: Attendance was excellent (6 of 9 patients attended ≥7 of 10 classes). Patients reported high satisfaction and overall benefit of the MBI. The intervention was effective in reducing emotional eating at 6 months (−4.9 ± 13.7 in mindfulness vs. 6.2 ± 28.4 in standard, p for between-group difference = 0.03) but not weight. We also observed a significant increase in HbA1C (0.34 ± 0.38 vs. −0.06 ± 0.31, p = 0.03). Objective measures suggested trends of an increase in perceived stress and symptoms of depression, although patients reported reduced stress reactivity, improved eating behaviors, and a desire for continued mindfulness-based support in qualitative interviews. Conclusions: This novel mindfulness-based approach is highly acceptable to bariatric patients post-surgery and may be effective for reducing emotional eating, although it did not improve weight or glycemic control in the short term. Longer-term studies of mindfulness-based approaches may be warranted in this population. Clinical trial registration: ClinicalTrials.gov identifier NCT02603601.